Konstruksi Perempuan Dalam Budaya Melayu (Studi Terhadap Perempuan Pengusaha UKM Di Kota Palembang : Pendekatan Ekonomi Dan Agama) - Juwita Anggraini (An Nisa'a, 2017)
This study discusses the Construction of Malay Woman Entrepreneurs. This research departs from the beginning of Malay Women with qualities such as self-satisfaction, lack of full, inefficient in doing things, lack of respect for time, lack of imagination and less persistent in effort. Tabrani further describes this ethnic decline caused by their characteristic that can be formulated: (1) the ability to compete in this tribe is very small, (2) Poverty is a common food, (3) Shadow of lack of quality food, replace the peat land blocking rice crops to flourish, (4) satisfaction towards the results achieved and strongly bound family groups that are difficult to develop, and (5) educational patterns that do not lead them to lead generation Problem formulation of the Women's Construction in Malay Culture on Women Entrepreneurs. Data Source is the primary source of results from interviews with some narasimber. Secondary sources are examined from the data of books relating to Women and Construction The results of this study review the values of Malay women entrepreneurs ie, diligent in running a business, have a good time management, high creativity in product development in the right. In the division of gender roles, it is seen that Malay women have no significant advantages in performing their role both as mother and wife as well as a businessman. All benefits in the division of labor are addressed wisely. Among them are caregivers at the same place in business, division of domestic role with husband and so forth. In women's capacity building and business development, Malay women mostly perform their capacities by participating in government programs and self-reliant institutions. With the development of capacity, it is easy for Malay women to formulate stratehi of business development.